A Pediatric Case of Visceral leishmanisis - Kuk, Salih; Poyrazoğlu, Gamze; Arslan, F. Necati; Erensoy, Ahmet; Akarsu, Saadet (Fırat University, 2007)
Visceral leishmaniasis (VL) is a disease caused by protozoan parasites of the genus leishmania. A eight-year old female patient who had hepatosplenomegaly was referred to Fırat Medical Centre by the Bingöl State Hospital. Leishmania amstigotes were seen in a smear prepared from bone morrow and stained with Giemsa. Leishmania IgG ELISA and Formol Gel test were positive. We hope that our case contributes the physicians to be aware of visceral leishmaniasis and its diagnosis. ©2007, Firat University, Medical Faculty

Visceral leishmaniasis leishmania türü parazitler tarafından oluşturulan protozoan bir hastalıktır. Bu çalışmada, Bingöl Devlet hastanesinden Fırat Tıp Merkezine hepatosplenomegali nedeniyle sevk edilen 8 yaşında kız hasta sunulmuştur. Hastanın Giemsa ile boyanmış kemik iliği yaymasında leishmania amastigotlarının görülmesi ve Leishmania IgG ELISA ve Formol Gel testinin pozitif olmasıyla visceral leishmania tanısı konulmuştur. Bu olgu sunumu ile visceral leishmania'ya, tanısında çekilen zorluklara ve çözüm yollarına katkı sağlanacağını ümit ediyoruz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Bir Çocukta Visceral Leishmaniasis Olgusu